Islamic Views on the position of women in Law and Society - Ajeng Casika; Dinda Agil Noviyana; Nela Melani; Siti Perawati; Pipit Nurhayati; Windi Rahmawati; Masduki Asbari; Dewiana Novitasari; Agus Purwanto (Journal of Community Service and Engagement, 2022)
This study aims to describe the cultivation of the thought that women are considered inferior in position to men is at the root of the problem of gender inequality that still occurs today, not only in Indonesia but also around the world, to erode the thinking of a society that has been firmly entrenched, it takes a thorough effort from various sides, including religion. This study uses data collection tools from articles on Google Scholar and google.com. The method of delivering material in this activity is through Zoom Meetings with students at one of the universities in Tangerang. Gender equality from the perspective of Islamic teachings, men and women already have their innate nature and character since birth that is different both physically and psychologically, with such differences that do not mean that according to Islam men are superior or inferior to women but only show the existence of different forms of phishing and psychic or character, as well as their rights that should be the same as men but in reality women many are limited to their rights in society. This research shows that gender equality and woman's rights intelligence is very important to implement because it contains religious character value-based character education.